Use of dump rocks in backfill mixtures while mining iron-ore deposits - Petlovanyi, M.V.; Ganushevych, K.A. (My University, 2021)
The article is devoted to topical issues of increasing the volume of utilization of mine rocks in backfill mixtures on the basis of improving their properties and component composition to improve technological features and environmental consequences.
Keywords: backfill mixture; dump rocks, strength, utilization